Pharmacogenetics in Veterinary Medicine: Part I - Suthamnatpong, Naowarat; Ponpornpisit, Aranya (Journal of Mahanakorn Veterinary Medicine, 2022)
Similar to human being, animal patients vary widely in their responses to medications. Variation in drug response often causes problems in the treatment since it can result in unpredictable and variability of therapeutic efficacy and sometimes serious adverse drug reactions. One of the key factors that contributed to variation in drug responses is the genetic factors, especially genetic polymorphism of the proteins that play an important role in pharmacokinetics and pharmacodynamics. The aim of this article is to provide useful information on veterinary pharmacogenetics. In part I of the series we focused on the basic knowledge in pharmacogenetics, the different forms of variation in drug responses, and the pharmacogenetics of ABCB1 which is a member of ATP-driven drug efflux carriers. In part II of the series, we focused on the cytochrome P450 enzymes which play an important role in pharmacokinetics of drugs commonly used in veterinary medicine and the application of genetic testing in veterinary clinical practice.